Tailor made degradable ureteral stents from natural origin polysaccharides - Barros, Alexandre A. (2013)
A urinary stent is defined as a thin tube, which is inserted in the ureter to prevent or treat the obstruction of urine flow from the kidney. Silicone, latex, polyvinylchloride and polyurethanes are the most widely used materials for the preparation of stents. Nonetheless, severe clinical complications may result from the use of these materials such as fracture, encrustation and infection. In some of the cases, the ureteral stents are temporary and it is often required a second surgery to remove the stent. The main complications with ureteral stents are dislocation, infection, and blockage by encrustation [1]. Recently, a tendency has been noticed favouring less invasive approaches (e.g. pharmacological or catheterization) in treating patients who exhibit symptoms or signs of urinary retention [2]. Currently, nearly 100% of the people who have an urological stent are likely to develop a bacterial infection within 30 days, which increases morbidity threefold [1]. Different types of temporary and permanent stents have been introduced into urological practice to relieve obstructions [3]. Particular attention should be devoted to polymers as they represent a highly versatile class of materials. Despite the fact that silicon continues to be the gold standard material for urological stents, there have been fast developments in manufacturing processes, as well as the introduction of new biodegradable materials in order to overcome the drawbacks of the available products. Polyurethane continues to be the most widely used material for polymeric stents; however it frequently promotes biofilm formation and bacterial adhesion leading to severe infections [2]. The concerns regarding existing stents are the motivation to design new biodegradable urological stent systems based on natural polymers, specifically polysaccharides, which present inherent biocompatibility, anti-bacterial properties and that can be tailor-made into a custom suitable stent for a particular patient.